Employee Development Model Through Work Motivation at PT. Rajawali Nusindo Padang Branch - Novi okta viara; Mondra Neldi; Chintya Ones Charli (Journal Of Management Analytical and Solution (JoMAS), 2024)
The This research aims to determine and attempt to analyze the influence of competency and work placement on employee development with work motivation as an intervening variable at PT. RajawaliNusindo Padang Branch. This research is a Structural Equation Modeling (SEM) model with the SmartPLS3.0 analysis tool. The population and sample of this research are employees of PT. Rajawali NusindoPadang Branch. The research results found that there is an influence between competency and work motivation. There is no influence between Job Placement and Work Motivation. There is no influence between Competency on Employee Development. There is no influence between Job Placement and Employee Development. There is an influence between Work Motivation on Employee Development. Work Motivation mediates Competence on Employee Development. Work Motivation does not mediate Job Placement on Employee Development.